A review of the efficacy of anti-bullying programmes in Spain - Sarasola Gastesi, Maitane; Ripoll Salceda, Juan Cruz (Pulso. Revista de educación, 2019)
Much research on bullying has been carried out in the last decades, and experts in this field have designed a great variety of programmes to fight this type of violence in schools. With the aim of knowing the efficacy of Spanish anti-bullying programmes, a review of evaluations of these programmes has been carried out, and a total of 11 research studies have been selected. The review shows both problems with the design of the interventions and also varied results which, most of the times, are not statistically significant. Nevertheless, one of the reviewed programmes shows a higher degree of consistency.
Keywords: Bullying; Ciberbullying; Intervention Programmes; Review